2007
DOI: 10.2471/blt.07.040162
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive injections by community health workers in Uganda: a nonrandomized community trial

Abstract: Objective To compare the safety and quality of contraceptive injections by community-based health workers with those of clinicbased nurses in a rural African setting.Methods A nonrandomized community trial tested provision of injectable Depo Provera (DMPA) by community reproductive health workers and compared it with routine DPMA provision at health units in Nakasongola District, Uganda. The primary outcome measures were safety, acceptability and continuation rates. Findings A total of 945 new DMPA users were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 4 publications
0
103
1
1
Order By: Relevance
“…2,9 While several countries have experimented with shifting the distribution of short-term methods of family planning to community-based distributors or health volunteers, [10][11][12] much unmet need for contraceptives remains. 13 Shifting the task of providing longer-acting injectable contraceptives, such as depot medroxyprogesterone acetate (DPMA), to community workers can provide access to these methods to a larger number of women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9 While several countries have experimented with shifting the distribution of short-term methods of family planning to community-based distributors or health volunteers, [10][11][12] much unmet need for contraceptives remains. 13 Shifting the task of providing longer-acting injectable contraceptives, such as depot medroxyprogesterone acetate (DPMA), to community workers can provide access to these methods to a larger number of women.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, studies conducted in Madagascar, Malawi and Uganda have demonstrated that community health workers who receive proper training in screening, injection technique and counselling can administer DMPA injections to women in rural areas just as safely as clinic-based providers and with comparable rates of acceptability and continuation. 11,12,[16][17][18] In numerous settings, DMPA has emerged as the preferred method of contraception primarily because it is effective, can be used privately, has a longer period of action than oral contraceptives or condoms and requires less frequent supply. 19 In Ethiopia, DMPA is now the method of choice for over 70% of women using modern methods of contraception, compared with almost no utilization as recently as 1990.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 In low-income countries, injectables have several advantages: they require minimal provider training and do not require patient follow-up beyond the woman returning regularly for repeat injections. 5,6 Furthermore, injections can be more easily concealed from partners than pills and other methods. Lastly, injectables are effective: less than 1% of women become pregnant within a year with consistent use; 3% with inconsistent use.…”
mentioning
confidence: 99%
“…11,12 Recent community trials in Uganda show that CHWs compare favourably with clinics in standards of care for providing injectables. 13 Study limitations include lack of a formal control group. However, having no competing inputs, changes can be attributed to the ACU Project.…”
Section: Summary Of Main Lessons Learntmentioning
confidence: 99%